Characterization of mice carrying Rmrp 71A>G, the causative mutation of cartilage-hair hypoplasia - Raimoranta, Inka (My University, 2023)
Cartilage-hair hypoplasia (CHH) is a severe disease that causes short stature and abnormal immune system function and predisposes patients to many health issues, such as malignancies. There is no cure for CHH, and treatment is limited to alleviate the symptoms. The pathology behind the RMRP 71A>G mutation induced disease is largely elusive, and the lack of CHH animal models is a remarkable obstacle in studying the disease. Our group therefore created a novel CHH mouse model by introducing the mutation into the mouse genome; however, embryos homozygous for the mutation die during embryogenesis. Moreover, we had observed an increase in the mortality rate of heterozygous carrier mice, which led us to hypothesize they might recapitulate some phenotypes associated with CHH. The aims of this thesis study were 1) to evaluate whether adult heterozygous mice recapitulate some qualities of the Finnish CHH, and thus, if the model is suitable to be used in future studies of cartilage-hair hypoplasia, and 2) to determine the time of death of homozygous embryos and to study the underlying mechanisms of embryonic lethality. To evaluate the suitability of heterozygous mice in modelling CHH, their Rmrp expression levels were quantified. There were no significant differences in Rmrp expression between wildtype and heterozygous animals, nor did we observe any health issues or more deaths of heterozygotes, suggesting that they likely are not suitable for studying phenotypes associated with CHH. The time of death of the homozygous embryos was determined by harvesting and genotyping embryos at different time points, and mechanisms behind the lethality were studied by analysing gene expression, and doing immunohistochemistry and wholemount immunofluorescence. The homozygous embryos died around embryonic development day 8.5 to 9.5, when significant developmental distortion was observed. The embryos appeared to have been arrested at the egg cylinder stage and fail gastrulation. The failure to gastrulate may be caused by lack of a properly committed extraembryonic ectoderm; however, mechanisms behind the embryonic lethality should be studied further. Embryos at earlier developmental days should also be analysed to detect whether there are issues in development prior to gastrulation.
Keywords: Cartilage-hair hypoplasia, RMRP, RNase MRP, embryonic lethality